(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: PE is a pregnancy-related syndrome with Gestational hypertension and proteinuria. It is caused by improper maternal spiral artery remodelling leading to reduced perfusion to the placenta, promoting exaggerated inflammatory markers CRP, IL 6, TNF alpha, and oxidative stress (OS) tags (MDA) into circulation. Therefore, this study was planned to explore any association between telomere length, inflammatory markers, and oxidative stress markers with change in BP (increase every ten mmHg). To the best of our knowledge, it is the first study exploring this association in preeclamptic patients. Methods: A case-control study included PE cases (n=90) and controls (n=70). RT-PCR measured relative telomere length (RTL) as a T/S ratio. Serum levels of Malondialdehyde (MDA) and C-reactive protein (CRP) by using competitive ELISA and uric acid (UA) levels by autoanalyzer. Results: RTL is significantly(p=.000) reduced in PE compared to control. MDA, CRP, and Uric acid levels significantly(p=.000) increased in cases than in control. Telomere length decreased with the rise in BP, and CRP, MDA, and UA levels increased significantly with an increase in BP. Therefore, we planned to explore the association between telomere length, inflammation, and oxidative stress with every ten mmHg increase in BP. Conclusion: Increasing BP by ten mmHg led to shorter Telomere Length and increased MDA, CRP, and UA levels. Therefore, increasing BP is associated with shorter telomere length, oxidative stress, and inflammation in PE.